Riso sagrado: a comicidade como estratégia discursiva na midiatização da religião - Regiani, Herivelton (2022)
The research deals with comicity as a discursive strategy in Christianity, pointing to an intensification of the presence of humour and laughter in religious environments. This intensification is understood as a phenomenon integrated to the mediatization of society and, specifically, to the mediatization of religion. The construction of comic humour is seen in its relationship with the discursive circulation (BRAGA, 2006; 2017; VERÓN, 2004; FAUSTO NETO, 2008; 2018), highlighting it as a communicational problem that has received greater attention in the face of the increasingly complex and diffuse interactions that characterize the ongoing mediatization. New ways of being, living and doing emerge, as well as new forms of religiosity, with flows that open up to previously unimagined possibilities in terms of discourses and social practices. This work presents reflections on the relationship between religion and communication and on the media nature of religion, as well as on the place of religion in contemporary times. It also addresses, from a historical perspective, the tensions between humour and religion in Christianity. It also reviews the theoretical approaches to humour, especially those that contribute to the understanding of its discursive aspects. As for the empirical research, two social actors are highlighted: the Catholic priest Fábio de Melo and the Protestant pastor Cláudio Duarte. These were chosen because they are emblematic of the two main branches of Brazilian Christianity, and because they build unique and diverse ways of adopting humour as a strategy for building bonds with their audiences. Different communicational attempts in the production of these social actors are followed, especially between the years 2017 and 2021, identifying discursive marks of the construction of different forms of comicity, also influenced by an intense interdiscursive circulatory activity. The analysis methodology takes as its starting point the socio-discursive semiological perspective (VERÓN, 2004), making use of other concepts, such as ethos (MAINGUENEAU, 2015) and performance, (GOFFMAN, 2002) in addition to theoretical references about what is proper to humour, laughter and comicity. From the effects of meaning (VERÓN, 2004) identified in the recurrent marks of the activity of these social actors in media platforms (FERNÁNDEZ, 2018), the strategies that act towards the constitution and maintenance of reading contracts (VERÓN, 2004; FAUSTO NETO, 2007) are highlighted. In these contracts, social actors establish unique ways of approaching their audiences, surprising them with different pastoral postures in relation to those traditionally experienced. In their enunciative activity, they alternate between the comic and the serious in order to effect reflections or prescriptions for the lives of their followers. However, they keep differences with each other in terms of ideological affiliations, which results in more open and reflexive forms of comedy, in the case of Fábio de Melo, or more conservative and prescriptive, in the case of Cláudio Duarte.